Plan estratégico para la empresa Audio y Video Jefferson en la ciudad de Catamayo Provincia de Loja periodo 2022-2027 - Asadobay Torres, Jessenia Elizabeth (2023)
The purpose of this study is to increase the demand and coverage of a business market case, the general objective was to develop a strategic plan for the period 2022-2027 for the company "Audio and Video Jefferson", located in Catamayo, Province of Loja. The study was carried out with a mixed research approach. The methods used were analytical-synthetic, statistical as well as inductive-deductive, allowing to break down elements and relate their characteristics to analyze internal and external factors for the development of the strategic plan. In order to gather information, techniques such as interviews and questionnaires were used. The external and internal diagnosis allowed to identify the opportunities and threats, weaknesses and opportunities according to the following elements: Economic, Political, Social, Technological, Legal and environmental. Through PORTER's five forces, the MEFE matrix was made for the findings obtained, which shows a value of 3.05, considering that the reference value is 2.5. For the intrinsic study of the company, interviews were carried out with both the manager of the company and the workers, a questionnaire was applied to external clients and when weighing the elements in the MEFI matrix, the finding was 3.85, which means that the advantages outweigh the disadvantages. The cost of the application and the development of these strategic objectives is 8,240 dollars and it is concluded that the company is well consolidated taking into account that the strengths outweigh the weaknesses; likewise, great opportunities were evidenced, which allows reducing threats. Keywords: Strategic Plan, business market, company